Falling labour share and anaemic growth in Portugal: A post-Keynesian econometric analysis - Alcobia, J.; Barradas, R. (Economic and Labour Relations Review, 2023)
In recent decades, the labour share has experienced a downward trend in Portugal at the same time as a weaker and anaemic growth pattern. This seems to suggest that the fall in the labour share represents an important constraint on Portuguese economic growth, which is contrary to the orthodox claims around wage restraint policies – namely, that such policies are a necessary condition of improved macroeconomic performance, owing to their positive effects on private investment through higher profits and on net exports through reduced unit labour costs and a corresponding rise in competitiveness. This study assesses the relationship between labour share growth and economic growth by performing a time series econometric analysis focused on Portugal from 1971 to 2021. Findings show that labour share growth has positively impacted on economic growth in Portugal, which is in line with heterodox claims and particularly with post-Keynesian economics on the beneficial effects on private consumption played by the growth of wages. Findings also confirm that the Portuguese economy has followed a wage-led growth regime instead of a profit-led growth regime; that is, a rise in wages increases aggregate demand and, therefore, boosts economic growth because its beneficial effect on private consumption more than compensates for a prejudicial effect on private investment and on net exports. The study points out the urgent need to adopt public policies to support the growth of wages to avoid more decades of dismal growth and a new ‘secular stagnation’ in Portugal.